Formation of priorities for the public education management system development - Diachenko, Svitlana; Buha, Volodymyr; Shchetinina, Tetiana; Olentiev, Roman; Uhodnikova, Olena (Linguistics and Culture Review, 2021)
In the context of global challenges, the problems of the education system become much more acute. Access to quality education for a number of categories of the population is limited due to financial, political, religious and social problems. The solutions to these problems lie within the competence of the governing bodies of the education system at the state level. The article identifies the duality of the problem of ensuring the quality of education. The article presents the results of a questionnaire survey to ensure the quality of training in the system of public education management. Accordingly, the respondents defined their position on the following issues: assessment of the current system of training for public administration, determination of basic qualifications and characteristics that should be possessed by specialists in the public administration system specializing in education, identification of priorities and problems in education.